Organogel investigations as a floating oral system with depot property - Zainab Saad Kaddoori; Masar Basim Mohsin Mohamed; Nawfal Am. Numan (College of Pharmacy / Mustansiriyah University, 2022)
In this work we investigate span 40, span 60 and SA as a gelators and olive oil (OO) as apolar liquid phase to discover the ability of organogel formed to be floating in acidic media and gain a unique gastroretentive dosage form. In addition, take advantage of the chemical   and physical properties of cinnarizine (CN) as a model drug suitable for gastroretentive systems. The floating parameters were studied where the floating lag time and floating duration for organogel in both solid and liquid states. Organogels charecterization were accomplished through the folowing investigatational techniques and analytical methods: table top rheology, optical microscope, Fourier-transform infrared spectroscopy (FTIR) and in- vitro release study. The results showed that all organogels immediately floated and they were floating in both states. Moreover, table top rheology showed that the transition temperature was reversible and higher than 37 ºC except for 7% w/w and 10% w/w SA in OO organogels where, optical images of organogel showed fibrillar network. The FTIR showed peaks associated to carbonyl groups indicated to form gelator-gelator interactions. Moreover, in vitro release study of organogel system showed continuous release CN for 9-12 hours.